WANARA IN RAMAYANA SHADOW PLAY: REPRESENTATION OF HUMANISM, VISUAL COMMUNICATION, AND CONTEMPORARY CULTURE - Febrianto Saptodewo; Sandra Olifia; Iwan Gunawan; Vickrie Ardy (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study explores the representation of Wanara characters in Javanese Wayang kulit Ramayana from the perspectives of Visual Communication Design (DKV), communication science, and humanistic values. Wanara, meaning